2008
DOI: 10.1063/1.2937936
|View full text |Cite
|
Sign up to set email alerts
|

Shock compression of condensed matter using Eulerian multimaterial method: Applications to multidimensional shocks, deflagration, detonation, and laser ablation

Abstract: The reactive flow analysis of high energy material is performed using hydro shock compression of condensed matter (SCCM) tool that is being developed for handling complex multimaterial dynamics involving energetic and inert matters. Typically, the reacting flows of high energy materials such as fires and explosions give rise to strong nonlinear shock waves and high strain rate deformation of metallic confinements at unusually high pressure and temperature. In order to address difficulties associated with analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…13 A level-set based reactive Ghost Fluid Method (GFM) that imposes exact boundary conditions at material interfaces is developed to reproduce the experimental size effect data of the unconfined rate stick tests.…”
Section: Rate Stick Simulationmentioning
confidence: 99%
“…13 A level-set based reactive Ghost Fluid Method (GFM) that imposes exact boundary conditions at material interfaces is developed to reproduce the experimental size effect data of the unconfined rate stick tests.…”
Section: Rate Stick Simulationmentioning
confidence: 99%
“…These parameters have been fitted to the ODTX data to establish accurate deflagration kinetics for each energetic sample tested. For a full description of the basic theory of thermal ignition modeling of RDX and HMX, readers may find the papers [6,7] informative. On the other hand, the thermal response of AP/HTPB is newly built in this work by utilizing the material data of AP/HTPB composite propellant in Tables 2 and 5.…”
Section: Ignition Via Thermal Heating -Testing Of Deflagration Kineticsmentioning
confidence: 99%
“…In order to describe the thermo-chemical response of energetic materials upon frictional loading, two distinct aspects of present study are identified: first, the chemical reaction of the condensed energetic material is modeled through the thermal decomposition kinetics that has been verified through a series of scaled explosion tests [6,7]. The second aspect of this work includes the mechanical ignition by friction experiments performed on the BAM apparatus.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, blast waves generated by short-pulse relatively high-intensity lasers had already been studied in gases. Works had focused on generating high Mach number blast waves (Edens et al 2004), studying deflagration and detonation (Yoh et al 2008) and realizing experiments in the framework of laboratory astrophysics (Moore et al 2005). Blast waves were also observed in solids (Budil et al 2000) using a very high-energy petawatt laser at Livermore, where the involved mechanism was not discussed in detail.…”
Section: High-energy Density Physics and Laboratory Astrophysics Drivmentioning
confidence: 99%